Vascular tumors in livers with targeted inactivation of the von Hippel–Lindau tumor suppressor - Haase, Volker H. (The National Academy of Sciences, 2001)
von Hippel–Lindau (VHL) disease is a pleomorphic familial tumor syndrome that is characterized by the development of highly vascularized tumors. Homozygous disruption of the VHL gene in mice results in embryonic lethality. To investigate VHL function in the adult we have generated a conditional VHL null allele (2-lox allele) and null allele (1-lox allele) by Cre-mediated recombination in embryonic stem cells. We show here that mice heterozygous for the 1-lox allele develop cavernous hemangiomas of the liver, a rare manifestation of the human disease. Histologically these tumors were associated with hepatocellular steatosis and focal proliferations of small vessels. To study the cellular origin of these lesions we inactivated VHL tissue-specifically in hepatocytes. Deletion of VHL in the liver resulted in severe steatosis, many blood-filled vascular cavities, and foci of increased vascularization within the hepatic parenchyma. These histopathological changes were similar to those seen in livers from mice heterozygous for the 1-lox allele. Hypoxia-inducible mRNAs encoding vascular endothelial growth factor, glucose transporter 1, and erythropoietin were up-regulated. We thus provide evidence that targeted inactivation of mouse VHL can model clinical features of the human disease and underline the importance of the VHL gene product in the regulation of hypoxia-responsive genes in vivo.